2008
DOI: 10.3758/pbr.15.1.156
|View full text |Cite
|
Sign up to set email alerts
|

Partial knowledge in a tip-of-the-tongue state about two- and three-word proper names

Abstract: Participants in this study attempted to name 44 famous people in response to reading biographical information about them. Half of the celebrities had names that contained two words (e.g., Gwyneth Paltrow and Sean Penn), and half of them had names containing three words (e.g., Catherine Zeta Jones and Billy Bob Thornton). Half of the names had previously been judged to be of high familiarity (e.g., Gwyneth Paltrow), and half were of lower familiarity (e.g., Billy Bob Thornton). The results showed that when in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 25 publications
3
20
0
1
Order By: Relevance
“…Our modest evidence indicates that perhaps a general (long/short), rather than specific (syllable number), sense of word length may be accessible for some higher-confidence unrecalled words. Such modest evidence is comparable to Hanley and Chapman's (2008) finding that accuracy in identifying word number in unretrieved celebrity names (two words, Gwyneth Paltrow; three words, Billy Bob Thornton) was only 7 % higher during TOTs (56 %) than during DKs (49 %). Interestingly, their DK performance was clearly at chance, similar to our UF and LF items in Experiment 2.…”
Section: Discussionsupporting
confidence: 56%
“…Our modest evidence indicates that perhaps a general (long/short), rather than specific (syllable number), sense of word length may be accessible for some higher-confidence unrecalled words. Such modest evidence is comparable to Hanley and Chapman's (2008) finding that accuracy in identifying word number in unretrieved celebrity names (two words, Gwyneth Paltrow; three words, Billy Bob Thornton) was only 7 % higher during TOTs (56 %) than during DKs (49 %). Interestingly, their DK performance was clearly at chance, similar to our UF and LF items in Experiment 2.…”
Section: Discussionsupporting
confidence: 56%
“…There is no evidence that using biographical descriptions should have any effect on the number of phonological retrieval failures for people's names. For example, Hanley and Chapman (2008) reported broadly similar TOT rates to those observed in Experiment 1 when participants were asked to identify celebrities from verbal descriptions.…”
Section: Methodsmentioning
confidence: 55%
“…Gollan and Brown (2006) showed that retrieval failure for phonological information about known items was more probable for common names of relatively low familiarity. Hanley and Chapman (2008) showed that the same is true for the names of people. This raises the possibility that common names would induce as many retrieval failures as people's names if the two were matched for preexperimental familiarity.…”
mentioning
confidence: 51%
“…Future research should examine whether participants use the TOT heuristic to infer other qualities and characteristics of the unretrieved target, such as the number of words in an unretrieved name (e.g., Hanley & Chapman, 2008), a word's length, or the likelihood that the word starts with a more versus a less frequent first letter or sound. Given the proposed role of partial attribute access in other metacognitive states, such as feelings-of-knowing (e.g., Nomi & Cleary, 2012), future studies should also examine whether similar heuristics are used with such other states.…”
Section: Discussionmentioning
confidence: 99%